The Law’s Majestic Equality? The Distributive Impact of Litigating Social and Economic Rights - Brinks, Daniel M. (2012)
Optimism about the use of laws, constitutions, and rights to achieve social change has never been higher among practitioners. But the academic literature is skeptical that courts can direct resources toward the poor. This paper develops a nuanced account in which not all courts are the same. Countries and policy areas characterized by judicial decisions with broader applicability tend to avoid the potential anti-poor bias of courts, whereas areas dominated by individual litigation and individualized effects are less likely to have pro-poor outcomes. Using data on social and economic rights cases in five countries, the authors estimate the potential distributive impact of litigation by examining whether the poor are over or under-represented among the beneficiaries of litigation, relative to their share of the population. They find that the impact of courts varies considerably across the cases, but is positive and pro-poor in two of the five countries (India and South Africa), distribution-neutral in two others (Indonesia and Brazil), and sharply anti-poor in Nigeria. Overall, the results of litigation are much more positive for the poor than conventional wisdom would suggest.